Change Management and Firm Performance of Selected Deposit Money Banks in Owerri, Imo State, Nigeria - K. E, Ugwu; H.E, Osisioma; L, Onwuzuligbo; N.C, Nnaji-ihedinmah (Journal of Empirical Studies, 2020)
This study examined the influence of change management on firm performance of deposit money banks in Owerri, Imo State. Descriptive survey design and the questionnaire were used in data collection. The total population comprised of 124 staff of Fidelity Bank, Access Bank, Eco-Bank and United Bank for Africa Plc. Out of 124 copies of the questionnaire administered to the participants, 116 were responded and used for the analysis, while, the remaining 6 were not returned and utilized. The research hypothesis was tested and analyzed using simple regression method to generate the result. The null hypothesis was rejected at 5 % level of significance. The study found that change management variable (leadership change) exerts a significant positive influence on firm performance (competitiveness) of banks in Owerri, Nigeria. The study recommends the followings; organizational leaders are advised to train their members in form of; coaching, counselling of other psychological support to encourage members to enforce change in the workplace. Again, managers are encouraged to communicate to all stakeholders effectively during corporate restructuring or redesigning of business process to enable them to see the necessity of change.